POSSIBILITIES OF ATTRACTION OF INVESTMENTS AND ALLOCATION OF RISKS IN PROJECTS USING THE MECHANISM PUBLIC-PRIVATE PARTNERSHIPS - O. Astafyeva; V. Dikih (Вестник университета)
The article describes a new form of attracting investment in infrastructure projects with using mechanisms of public-private partnerships. The risk allocation between the project participants, in order to minimize risk and avoid negative developments in the implementation of projects. Discusses the importance of technological and price audit to ensure effective cost solutions when implementing projects based on public-private partnerships.